Paralysed Digital Economy And The Role Of Youth In The Development And Simulation Of Creativity In Era 4.0 - Kalimanzila Matemani, James; Ma’ruf, Anwar Ma’ruf (Opción, 2019)
This study discusses the key factors that paralyse the younger generation in the context of economic thinking when they are using digital accessories and Internet services. Likewise, this study has demonstrated the way forward concerning how to handle this issue. Furthermore, this research found that numerous countries depend on youth economic charities as the key player of economic development, particularly in the digital era. The data was col- lected through both qualitative and quantitative methods using statistic tools and in-depth interviews. In conclusion, the paralysed digital economy can be removed through collective digital education and youth involvement in the digital economy, particularly in this technological and innovation era.